Identifying the barriers and facilitators to culturally responsive HIV and PrEP screening for racial, ethnic, sexual, and gender minoritized patients: A scoping review protocol. - Julia Xavier; Maranda C Ward; Patrick G Corr; Nikhil Kalita; Paige McDonald (PLoS ONE)
Introduction While mainstream messaging about human immunodeficiency virus (HIV) disparities continues to highlight individual risk-taking behavior among historically marginalized groups, including racial, ethnic, sexual, and gender minoritized patients, the effect of structural factors and social determinants of health (SDOH) on morbidity and mortality remain underestimated. Systemic barriers, including a failure of adequate and acceptable screening, play a significant role in the disparate rates of disease. Primary care practitioner (PCP) competency in culturally responsive screening practices is key to reducing the impact of structural factors on HIV rates and outcomes. To address this issue, a scoping review will be performed to inform the development of a training series and social marketing campaign to improve the competency of PCPs in this area. Objectives This scoping review aims to analyze what recent literature identify as facilitators and barriers of culturally responsive HIV and pre-exposure prophylaxis (PrEP) screening practices for historically marginalized populations, specifically racial, ethnic, sexual, and gender minoritized groups. A secondary aim is to identify themes and gaps in the literature to help guide future opportunities for research. Methods This scoping review will be performed following the framework set forth by Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). Relevant studies between the years 2019-2022 will be identified using a rigorous search strategy across four databases: MEDLINE (via PubMed), Scopus, Cochrane (CENTRAL; via Wiley), and CINAHL (via EBSCO), using Boolean and Medical Subject Headings (MeSH) search terms. Studies will be uploaded to the data extraction tool Covidence to remove duplicates and perform a title/abstract screening, followed by a full-text screening and data extraction. Results Data will be extracted and analyzed for themes related to culturally responsive HIV and PrEP screening practices in clinical encounters with the identified target populations. Results will be reported according to PRISMA-ScR guidelines. Discussion To our knowledge, this is the first study to use scoping methods to investigate barriers and facilitators to culturally responsive HIV and PrEP screening practices for racial, ethnic, sexual, and gender minoritized populations. The limitations of this study include the analysis restrictions of a scoping review and the timeframe of this review. We anticipate that this study's findings will interest PCPs, public health professionals, community activists, patient populations, and researchers interested in culturally responsive care. The results of this scoping review will inform a practitioner-level intervention that will support culturally sensitive quality improvement of HIV-related prevention and care for patients from minoritized groups. Additionally, the themes and gaps found during analysis will guide future avenues of research related to this topic.